2018
DOI: 10.1111/1749-4877.12310
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen supply did not affect how lizards responded to thermal stress

Abstract: Zoologists rely on mechanistic niche models of behavioral thermoregulation to understand how animals respond to climate change. These models predict that species will need to disperse to higher altitudes to persist in a warmer world. However, thermal stress and thus thermoregulatory behavior may depend on atmospheric oxygen as well as environmental temperatures. Severe hypoxia causes animals to prefer lower body temperatures, which could be interpreted as evidence that oxygen supply limits heat tolerance. Such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 64 publications
2
12
0
Order By: Relevance
“…A biogeographic shift to higher elevations is a common response of species to warming climates, at least where mountains are accessible (Colwell et al, 2008; Freeman and Freeman, 2014; Moritz et al, 2008; Parmesan, 2006). Such upward shifts enable organisms to track their thermal niche, but sometimes expose them to novel environmental conditions (Camacho et al, 2018) and species interactions (Angert et al, 2013). Over time the cumulative effect of these upward shifts may cause “biotic attrition” in lowland regions of the tropics, because the loss of lowland diversity caused by organisms shifting uphill is unlikely to be mitigated by new species moving in from lower latitudes (Colwell et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A biogeographic shift to higher elevations is a common response of species to warming climates, at least where mountains are accessible (Colwell et al, 2008; Freeman and Freeman, 2014; Moritz et al, 2008; Parmesan, 2006). Such upward shifts enable organisms to track their thermal niche, but sometimes expose them to novel environmental conditions (Camacho et al, 2018) and species interactions (Angert et al, 2013). Over time the cumulative effect of these upward shifts may cause “biotic attrition” in lowland regions of the tropics, because the loss of lowland diversity caused by organisms shifting uphill is unlikely to be mitigated by new species moving in from lower latitudes (Colwell et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Published physiological studies document that adult reptiles and amphibians typically lower their preferred temperature in response to extremely low, if ecologically unrealistic, oxygen levels (10%); and this is assumed to be physiologically beneficial by reducing aerobic stress (see review in Camacho et al 2018). Consequently, reduced oxygen at altitude might restrict dispersal to high elevation.…”
Section: Heterogeneity and Behavioral Evasionmentioning
confidence: 99%
“…Consequently, reduced oxygen at altitude might restrict dispersal to high elevation. Here Camacho et al (2018) examine whether ecologically relevant levels of oxygen influence the voluntary maximum temperature (rising temperature at which a lizard seeks escape) that lizards tolerate during laboratory heating. This evasive temperature is similar in 3 oxygen levels, suggesting that oxygen is not altering perceived thermal stress.…”
Section: Heterogeneity and Behavioral Evasionmentioning
confidence: 99%
See 1 more Smart Citation
“…In lizards, there is general support for OCLTT and/or HMTL hypotheses; numerous studies have demonstrated that exposure to hypoxic air causes lizards to select lower body temperatures and exhibit gaping and panting (to reduce body temperature via evaporative cooling) at lower temperatures than when breathing normoxic gas (Branco, Gargaglioni, & Barros, 2006; DuBois, Shea, Claunch, & Taylor, 2017; Petersen, Gleeson, & Scholnick, 2003; Shea et al, 2016). Additionally, adult lizards treated with severely hypoxic gas showed reduced CTmax (DuBois et al, 2017; Shea et al, 2016), and lizard embryos treated with hypoxic gas exhibited reduced survival (Smith, Telemeco, Angilletta, & VandenBrooks, 2015), but oxygen does not appear to limit thermal tolerance under mildly hypoxic or normoxic conditions (Camacho, Vandenbrooks, Riley, Telemeco, & Angilletta, 2018). There is less empirical support for upper thermal limit hypotheses under normoxic conditions, and much remains to be tested before CTmax is well‐understood in lizards.…”
Section: Introductionmentioning
confidence: 99%